A longitudinal case study of the training of the 2012 European 1500m track champion - Tjelta, L. I. (International Journal of Applied Sports Sciences, 2013)
The purpose of this study was to present the training of the European 1500 m track champion of 2012. Data from the training diaries were used to describe (a) the average training load (km/week-1), and (b) the distribution of training at different intensities based on his heart rate (HR) as a percentage of maximum heart rate(%HRmax) and on lactate measurements. In 2012, 68.5% of the total training load during the period from January to the middle of March was performed with HR between 65 and 75% of HRmax, 26.1% was performed as anaerobic threshold training, HR 82-92% of HRmaks and 3.8% was performed as aerobic high intensity training, HR 92-97% of HRmax. Only 1.5 % was performed as an aerobic training. During the track competition season, the percentage of training performed at low intensity increased to 73% as a result of some training loads at anaerobic threshold pace were replaced by some more intensive aerobic and anaerobic training sessions, requiring a lower training load. High proportion of interval training close to the anaerobic threshold might have led to excellent racing performance for this runner.